Determinan Kemiskinan Di Kabupaten Tuban - Agus Hari Pradita; Wahyu Hidayat Riyanto (Jurnal Ilmu Ekonomi, 2021)
The purpose of this research is to know the infulnce Product Domestic Regional Bruto (PDRB) and open unemployment rate on the number of poverty in Tuban Regency the period 2000-2019. The sampel in the study was taken from BPS as much 20 years. The research method used is a quantitative method. The analysis technique used multiple linear regression models with a significant  α 0,05 which was supported by the classical assumption test. The research results prove that PDRB variable has a negative and significant on the number of poverty. While the open unemployment rate variabel has a positive and significant on the number of poverty in Tuban Regency period 2000-2019.